Influence of shoes increasing dorsiflexion and decreasing metatarsus flexion on lower limb muscular activity during fitness exercises, walking, and running - Bourgit, D.; Millet, G. Y.; Fuchslocher, J. (The Journal of Strength and Conditioning Research, 2008)
The aim of the present study was to compare electromyographic activity during fitness exercises, walking, and running among 3 different dorsiflexion shoes (+2°, +4°, and +10°) and standard shoes (-4°). The 3 different dorsiflexion shoes tested in this study have a curvature placed in the middle of the sole. This design was specially projected to decrease the metatarsus flexion. Electromyographic activity of 9 lower limb muscles was measured on 12 healthy female subjects during 5 fitness exercises (unload squat, side and front step, submaximal ballistic plantar flexion, and lunge exercise), and during running (10 km·h-1) and walking (4.5 km·h-1) on a treadmill. EMG signal was analyzed with the root mean square (RMS) and integrated EMG. All RMS data measured during these exercises were expressed as percentages of maximum voluntary isometric contraction. The results show that dorsiflexion affects muscle recruitment and reorganizes the motor pattern. The general tendency was that the tibialis anterior activity increased with dorsiflexion. However, an optimal dorsiflexion existed for various exercises. It is concluded that shoes with moderate dorsiflexion can activate lower limb muscles differently compared with both standard shoes and shoes with large dorsiflexion during submaximal exercises and locomotion.